Respuesta :

Answer:

The solution of the differential equation is [tex]B=5+25e^{-4t+4}[/tex]

Step-by-step explanation:

The differential equation [tex]\frac{dB}{dt}+4B=20[/tex] is a first order separable ordinary differential equation (ODE). We know this because a separable first-order ODE has the form:

[tex]y'(t)=g(t)\cdot h(y)[/tex]

where g(t) and h(y) are given functions.

We can rewrite our differential equation in the form of a first-order separable ODE in this way:

[tex]\frac{dB}{dt}+4B=20\\\frac{dB}{dt}=20-4B\\\frac{dB}{dt}=4(5-B)\\\frac{1}{5-B}\frac{dB}{dt}=4[/tex]

Integrating both sides

[tex]\frac{1}{5-B}\frac{dB}{dt}=4\\\frac{1}{5-B}\cdot dB=4\cdot dt\\\\\int\limits {\frac{1}{5-B}} \, dB=\int\limits {4} \, dt[/tex]

The integral of left-side is:

[tex]\int\limits {\frac{1}{5-B}} \, dB\\\mathrm{Apply\:u-substitution:}\:u=5-B\\\int\limits {\frac{1}{5-B}} \, dB=\int\limits {\frac{1}{u}} \, dB\\\mathrm{du=-dB}\\-\int\limits {\frac{1}{u}} \,du\\\mathrm{Use\:the\:common\:integral}:\quad \int \frac{1}{u}du=\ln \left(\left|u\right|\right)\\-\int\limits {\frac{1}{u}} \,du =-\ln \left|u\right|\\\mathrm{Substitute\:back}\:u=5-B\\-\ln \left|5-B\right|\\\mathrm{Add\:a\:constant\:to\:the\:solution}\\-\ln \left|5-B\right|+C[/tex]

The integral of right-side is:

[tex]\int\limits {4} \, dt = 4t + C[/tex]

We can join the constants, and this is the implicit general solution

[tex]-\ln \left|5-B\right|+C=4t + C\\-\ln \left|5-B\right|=4t + D[/tex]

If we want to find the explicit general solution of the differential equation

We isolate B

[tex]-\ln \left|5-B\right|=4t + D\\\ln \left|5-B\right|=-4t+D\\\left|5-B\right|=e^{-4t+D}[/tex]

Recall the definition of |x|

[tex]|x|=\left \{ {{x, \:if \>x\geq \>0 } \atop {-x, \:if \>x<\>0}} \right.[/tex]

So

[tex]\left|5-B\right|=e^{-4t+D}\\5-B= \pm \:e^{-4t+D}\\B=5 \pm \:e^{-4t+D}\\B=5\pm \:e^{-4t}\cdot e^{D}\\B=5+Ae^{-4t}[/tex]

where [tex]A=\pm e^{D}[/tex]

Now B(1) =30 implies

[tex]B=5+Ae^{-4t}\\30=5+Ae^{-4}\\30-5=Ae^{-4}\\25e^{4}=A[/tex]

And the solution is

[tex]B=5+(25e^{4})e^{-4t}\\B=5+25e^{-4t+4}[/tex]

ACCESS MORE